Export Market Exit and Financial Health in Crises Periods - Holger Görg; Marina-Eliza Spaliara (Kiel Centre for Globalization (KCG), 2017)
This paper uses rich firm-level data for the UK to investigate the link between firms' financial health and export exit, paying attention to the ERM currency crisis and the global financial crisis. Our results show that deterioration in the financial position of firms has increased the hazard of export exit during the 2007-09 crisis but has no significant effect on the early 1990s crisis. We also explore the extent to which firms in financially vulnerable industries face greater sensitivity of export exit to financial conditions. We conclude that firms in sectors with great reliance on external finance experience higher hazards of exiting the export market during the 2007-09 crisis.
Keywords: F1; L2; G3; 330; financial health; financial vulnerability; exports; extensive margin; crises